Proposal for a General Allocation of SDRs. (Policy Papers; Policy Paper ;, 2009)
Faced with a global crisis of exceptional magnitude, the membership of the IMF has called for ambitious steps to strengthen the global financial safety net. These include, alongside efforts to strengthen the Fund's lending capacity, an allocation of SDRs equivalent to USD 250 billion to become effective well before the 2009 Annual Meetings. This call recognized that an SDR allocation is a prime example of cooperative monetary response to a global predicament. As such it would build confidence by adding to other concrete evidence of the international community's commitment to a collaborative response to the crisis. This paper follows up on the IMFC's request, in its Spring 2009 communique, for the IMF to put forward a concrete proposal assessing the case for such a USD 250 billion allocation and describing how it could be implemented.